Revalidation Physical Self-Perceptions: A Cross-Cultural Assessment in Indonesian Children - Akhmad Sobarna; Ahmad Hamidi; Agus Ahmad Bunyami; Asep Nirwan Muharam; Denok Sunarsi (Universitas Negeri Makassar, 2020)
The purposes of this research was to examined the cross-cultural validity of the Physical Self-Perception Profile for Children (PSPP-C), an instrument for assessing physical self-esteem, in Indonesian children. The inventory comprises 36-items designed to measure six constructs from a hypothesised multi-dimensional, hierarchical model of physical self-perception. Two hundred and fifty two children, aged 13 to 14 years, from a secondary school in Bandung- West Java completed the PSPP-C inventory. Descriptive statistics revealed mean construct scores to be comparable with results from other studies. Factor analysis of the inventory items supported a four factor structure and Cronbach alphas confirmed its internal consistency. The hierarchical structure of the underlying model was supported by partial correlation analysis. The PSPP-C exhibited satisfactory validity and reliability for use with children from Indonesia, but caution must be exercised when interpreting some of the subdomains due to discrepancies in the factor structure. The authors also express reservations concerning the indiscriminate use of such psychometric inventories across different cultures.